2020
DOI: 10.1177/0306624x20911899
|View full text |Cite
|
Sign up to set email alerts
|

Can Yoga Overcome Criminality? The Impact of Yoga on Recidivism in Israeli Prisons

Abstract: In recent years, yoga practices have been integrated into formal prison rehabilitation programs of the Israel Prison Service (IPS), as part of the informal education system, giving rise to innovative criminological theories such as positive criminology that emphasize the development of offenders’ strengths by facilitating rehabilitation and reintegration processes. The purpose of the present study was to examine the correlation between yoga practice and recidivism among released prisoners who participated in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Offender rehabilitation is a challenging goal that calls for creative innovations. Innovative spiritual-based methods such as yoga and meditation are considered to be effective methods (Barrett, 2016; Himelstein, 2011; Kovalsky et al, 2020; Norman, 2015; Ronel et al, 2013), however, they are typically applied in restricted and local programs. The aim of this paper is to present an application of the spiritual principle of non-doing in offender rehabilitation, where there is no stated intention to rehabilitate and no specific program , as practiced by the Islamic Sufi peacemaking route.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Offender rehabilitation is a challenging goal that calls for creative innovations. Innovative spiritual-based methods such as yoga and meditation are considered to be effective methods (Barrett, 2016; Himelstein, 2011; Kovalsky et al, 2020; Norman, 2015; Ronel et al, 2013), however, they are typically applied in restricted and local programs. The aim of this paper is to present an application of the spiritual principle of non-doing in offender rehabilitation, where there is no stated intention to rehabilitate and no specific program , as practiced by the Islamic Sufi peacemaking route.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it suggests dealing with crime through love, compassion, and empathy, indicating a nonviolent perspective of criminology and criminal justice that has the potential to end suffering, and thus to end crime (Pepinski, 2015). In the realm of crime and social deviance, we are acquainted with the desistance model through non-doing in rehabilitative groups that use Vipassana (Ronel et al, 2013) or yoga (Barrett, 2016; Kovalsky et al, 2020; Norman, 2015), and programs that involve modeling and reflective practices such as the twelve-step programs (Chen & Gueta, 2015; Ronel, 1998). Referring to the issue of the ownership of the criminal act, McNeill (2006) perceives probation practitioners as supporters of desistance processes (that belong to the desister) rather than providers of correctional treatment (that belongs to the expert).…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the educational experiences of prisoners during organized sports activities is scarce. The few studies that exist found that some specific sport interventions-from strength training to rugby or yoga classes-promote positive change in attitudes towards offending, help to reduce aggression levels and antisocial behavior, or lead to increased impulse control [17][18][19][20]. Furthermore, studies showed that sports programmes in prison can be a unique means to promote education [21] and contribute to learning rules and norms [22].…”
Section: Introductionmentioning
confidence: 99%